2020
DOI: 10.7717/peerj.8896
|View full text |Cite
|
Sign up to set email alerts
|

The role and proteomic analysis of ethylene in hydrogen gas-induced adventitious rooting development in cucumber (Cucumis sativus L.) explants

Abstract: Previous studies have shown that both hydrogen gas (H2) and ethylene (ETH) play positive roles in plant adventitious rooting. However, the relationship between H2and ETH during this process has not been explored and remains insufficiently understood. In this study, cucumber (Cucumis sativus L.) was used to explore the proteomic changes in ETH-H2-induced rooting. Our results show that hydrogen-rich water (HRW) and ethylene-releasing compound (ethephon) at proper concentrations promote adventitious rooting, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…ETH is a pleiotropic phytohormone, involving in a variety of developmental processes, such as rooting, ripening, and senescence in plants. A previous study reported that ETH may be another downstream signaling molecule in H 2 -promoted cucumber adventitious root formation [100]. Meanwhile, RuBisCO, SBPase, and OEE1 (photosynthesis-related proteins); TDH (amino acid metabolism-related protein); CAPX (stress response-related protein); and PDI (folding, modification, and degradation-related protein) might play important roles during these processes.…”
Section: H 2 Is Involved In Phytohormones Signalingmentioning
confidence: 99%
“…ETH is a pleiotropic phytohormone, involving in a variety of developmental processes, such as rooting, ripening, and senescence in plants. A previous study reported that ETH may be another downstream signaling molecule in H 2 -promoted cucumber adventitious root formation [100]. Meanwhile, RuBisCO, SBPase, and OEE1 (photosynthesis-related proteins); TDH (amino acid metabolism-related protein); CAPX (stress response-related protein); and PDI (folding, modification, and degradation-related protein) might play important roles during these processes.…”
Section: H 2 Is Involved In Phytohormones Signalingmentioning
confidence: 99%
“…These results indicated that MdIAA27 is a critical regulator of adventitious root development. Adventitious roots commonly increase the absorption area of roots and enhance their abilities to assimilate nutrients and support plants [45]. Previous studies have shown that adventitious roots promote phosphorus absorption under phosphorus deficiency conditions.…”
Section: Mdiaa27 Regulates the Number And Length Of Adventitious Root...mentioning
confidence: 99%